Evidence and impact of 2020 coral bleaching in West Lombok, Lesser Sunda Seascape, Indonesia - Ghafari, Muhammad Irsyad Abiyusfi (Universitas Malikussaleh, 2025)
Periodic El Niño phenomena have led to severe mass coral bleaching events for most of the world's tropical coral reefs. In 2020, despite being the warmest year in the last century, limitations on any activity during the COVID-19 pandemic caused coral bleaching events in Indonesia not to be documented very well. This study aims to provide evidence of the mass bleaching episode in 2020 and its impact on the coral benthic ecosystem at one of the COREMAP-CTI (Coral Reef Rehabilitation and Management Program – Coral Triangle Initiative) monitoring sites in West Lombok, Lesser Sunda Seascape, Indonesia. Integration of the locally brief monitoring results on coral bleaching indication in West Lombok, as well as the investigation on monthly sea surface temperature (SST), Spatial Bleaching Alert System data, and the results of delayed coral reef monitoring carried out in 2021 suggest that the coral bleaching may have occurred within the first quarter of 2020. That obscure bleaching event is believed to have contributed to the failure of recent coral recovery in West Lombok, in addition to anthropogenic pressure factors. Apart from the possible bleaching of corals in 2020, this indicates the need for the Indonesian government to establish more flexible monitoring systems that can be implemented even in difficult national situations, where a wide range of activities, such as the coral monitoring program, are restricted.